Exploring immunological alterations of B cells in peripheral immunity via single-cell RNA sequencing: insights into primary membranous nephropathy - Lu, Fang; Chen, Si; Guo, Honglei; Li, Qing; Wu, Lin; Pan, Ying; Wu, Yangfan; Shu, Hua; Liu, Simeng; Zhang, Bo; Mao, Huijuan; Xing, Changying; et al. (Frontiers in Immunology, 2025)
BackgroundPrimary Membranous Nephropathy (PMN) is characterized by dysregulated immune responses, with B cells playing critical roles in disease pathogenesis. However, the immunopathogenic mechanisms underlying B cell involvement in PMN remain elusive.MethodsWe employed single-cell RNA sequencing on peripheral blood mononuclear cell samples (PBMC) obtained from 6 patients with PMN and 3 healthy controls (NC) to explore the transformation of B cells and their interaction with immune cells.ResultsCompared with NC, the most significant alterations were in plasma cells and regulatory B (Breg) cells in PMN patients. Within plasma cells, Subcluster 0 was increased in PMN patients and exhibited enhanced autoimmunity. Breg subset B10 cells were elevated in PMN patients and displayed increased immune regulatory capacity, marked by enhanced cytokine and interleukin-10 production. B cell activating factor (BAFF) and galectin-9, which were secreted by CD14 monocyte, as potential regulators of plasma and Breg cells activity. Additionally, serum galectin-9 levels increased in PMN patients and showed a correlation with proteinuria and renal function in PMN.ConclusionsWe reveal novel insights into the heterogeneity and functional diversity of B cells in patients with PMN. And revealed distinct roles for subgroup 0 plasma cells and B10 Breg cells in the pathogenesis of PMN. Furthermore, targeting B cells, such as galectin-9, presents promising opportunities for modulating the immune response in patients with PMN.